GREEN FINANCE AS A CATALYST FOR TECHNOLOGICAL INNOVATION: A HETEROGENEOUS ANALYSIS OF EMERGING ECONOMIES - Munir, Saqib; Waheed, Khawaja Zeeshan (Economic Review: Journal of Economics and Business, 2025)
The role of green finance in driving technological innovation in resource-constrained emerging economies is examined. Despite substantial inflows, many nations struggle to convert funds into green technology advancements, prompting questions about finance-innovation mechanisms. Empirical evidence on heterogeneous impacts of green finance flows on technological innovation is extended, incorporating moderators like institutional quality, energy market dynamics, trade openness, and human capital development. Data from 2004–2023 across 10 BRICS economies (WDI, WGI) are analysed using fixed-effects panel regression and instrumental variable estimation. Renewable Energy Consumption (REC), a proxy for green finance, positively influences technological innovation; a 1% REC increase is associated with a 6.29% innovation rise. Strong institutions amplify this effect while trade openness unexpectedly weakens it. Energy intensity strengthens the linkage, whereas education expenditure negatively moderates it. Prioritization of institutional reforms and alignment of green finance with supportive policies are suggested to maximize technological innovation and advance sustainable development goals (SDGs). Regional variations and feedback loops should be validated to deepen the understanding of technological innovation dynamics.